Investigating Effects of COVID-19 Pandemic on the Mental Health of Nursing Students During Remote Learning: An Experience from Dong A University, Vietnam - Nguyen Thi Hai; Ha Lai Thi; Huyen Trang Tran Cong; Van Tran Thi; Le Oanh Hua Thi; Thanh Thuy Vo Le; Nga Pham Thi; Thuy Minh Do Thi; Thanh Huyen Nguyen Thi; Vu Chi Thi Quynh; Phu Tran Vinh Pham; Tran Thi My (SAGE Publishing, 2022)
Introduction There was a radically changed in nursing education during the nationwide lockdown due to the COVID-19 outbreaks. The transition to remote learning stressed nursing students in many countries, particularly in Vietnam. However, there is still lacking a novel study to describe the mental characteristics of nursing students in detail. Objectives To assess the mental health of nursing students, including stress, anxiety, and depression, and to identify the related factors to their mental health during the online study period because of the COVID-19 pandemic. Methods A cross-sectional survey was conducted on 540 nursing students at Dong A university using a socio-demographic questionnaire, the Depression, Anxiety, and Stress Scale - 21 Items (DASS-21). Data were analyzed by descriptive statistics and tests, including Mann-Whitney, Kruskal-Wallis, and Spearman's correlation to identify the related factors. Results In total 540 participants, nursing students reported stress (N  =  120, 22.2%), anxiety (n  =  195, 36.1%), and depression symptoms (n  =  135, 23.1%). There was a significant relationship between age, work status, married status, number of children, stress, anxiety, and depression (P < 0.01). In addition, our study showed a negative correlation between frequency of physical activity, perceived health and stress (r  =  -0.117; p < 0.01, r  =  -0.127, p < 0.01), anxiety (r  =  -0.133; p < 0.01, r  =  -0.112, p < 0.01), depression (r  =  -0.134; p < 0.01, r  =  -0.135, p < 0.01). A significant relationship was observed between e-learning space and Internet status with mental health (p < 0.05). Especially, there was no association between average online learning time, academic workload, stress, anxiety, and depression (p > 0.05). However, the authors found a positive association between perceived level of stress related to evaluative activities and stress, anxiety, depression (r  =  0.120, p < 0.01; r  =  0.089, p < 0.05; r  =  0.088, p < 0.05). Conclusion Nursing students suffered stress, anxiety, and depression during online learning due to the COVID-19 pandemic in the presence of some related factors. Therefore, this study may increase more attention of universities, families, and governments to reduce the stress of nursing students during distance education.